Pengaruh Penggunaan Teknologi Informasi, Pelatihan Penyusunan Laporan Keuangan, Dan Pengalaman Kerja Terhadap Kualitas Laporan Keuangan BUMDes Se – Kecamatan Marga - Ni Putu Eni Risnawati; Ni Komang Sumadi; Ni Wayan Alit Erlina Wati (UNHI Press, 2023)
This research aim to know the effect of using information technology, training of making finance report, and working experience toward the quality of BUMDes finance report in Marga sub-distrisct. The theory that used in this research is Theory of Planned Behavior and theory of agency. The population in this research are all of BUMDes employees in Marga sub-district with total 113 peoples. Total of sample in this research is 60 peoples determined by sampling purposive techniques, examined by using multiple linier regression techniques, and collecting the data with handing out quetionnaires. This result of this research showed that the used of information technology, training of making finance report and working experience which it gives positive infuential toward the quality of finance report. The suggestion be supposed to increase of updating on application, to arrange training of making finance report, and add working experience for BUMDes employee in Marga sub-district.